Benefit-Entitlement Effects and the Duration of Unemployment: An Ex-ante Evaluation of Recent Labour Market Reforms in Germany - Hendrik Schmitz; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We analyse benefit-entitlement effects and the likely impact of the recent reform of the unemployment compensation system on the duration of unemployment in Germany on the basis of a flexible discrete-time hazard rate model estimated on pre-reform data from the German Socioeconomic Panel. We find (i) relatively strong benefit-entitlement effects for the unemployed who are eligible to means-tested unemployment assistance after the exhaustion of unemployment benefit, but not for those without such entitlement; (ii) that benefit-entitlement effects on hazard rates are not monotonic in time to benefit-exhaustion but rather occur around the month of benefit-exhaustion, and (iii) relatively small marginal effects of the amount of unemployment compensation on the duration of unemployment. Simulation results show that the recent labour market reform is unlikely to have a major impact on the average duration of unemployment in the population as a whole, but will significantly reduce the level of long-term unemployment among older workers.
Keywords: J64; J65; H31; 330; unemployment duration; unemployment insurance; benefit-entitlement effects; German labour market reforms; ex-ante evaluation; hazard rate model